2018
DOI: 10.1021/acs.jafc.7b05009
|View full text |Cite
|
Sign up to set email alerts
|

Phytosterol Profiles of Common Foods and Estimated Natural Intake of Different Structures and Forms in China

Abstract: Phytosterols are well-known for their cholesterol-lowering effects, and the structures and forms of phytosterols affect their bioactivity. We aimed to illustrate the phytosterol profiles in common foods and estimate their natural intake in five geographical regions and among different age groups in China. In total, 12 phytosterols in free and esterified forms of 119 foods from five regions across China were examined using gas chromatography-mass spectrometry. Then, the dietary intake of phytosterols was calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 39 publications
(64 reference statements)
1
31
0
Order By: Relevance
“…Moreover, for chickpea and lentil, this content was reported as 2.05 and 1.58 mg g À1 , respectively [45]. Wang et al [46] revealed that the total phytosterol content was high in legume, with a content ranging from 1.30 to 2.8 mg g À1 . Moreover, they reported that the primary phytosterols in legumes were β-sitosterol, campesterol, and stigmasterol.…”
Section: Phytosterolsmentioning
confidence: 99%
“…Moreover, for chickpea and lentil, this content was reported as 2.05 and 1.58 mg g À1 , respectively [45]. Wang et al [46] revealed that the total phytosterol content was high in legume, with a content ranging from 1.30 to 2.8 mg g À1 . Moreover, they reported that the primary phytosterols in legumes were β-sitosterol, campesterol, and stigmasterol.…”
Section: Phytosterolsmentioning
confidence: 99%
“…A 2019 review demonstrated that consuming 500 mg/day of total phytosterols from foods could reduce cancer development risk [79], and a 37% risk reduction was seen for highest dietary phytosterol intake compared to the lowest intake [79]. Phytosterols are highest in vegetable oils (150.4-1230.9 mg/100 g), legumes (129.6-275.6 mg/100 g), and nuts (18.9-255.2 mg/100 g) [80].…”
Section: Cancermentioning
confidence: 99%
“…Wang et al studied the phytosterol profile and found total contents varying from 150.4 to 1230.9, 129.6 to 275.6, 18.9 to 255.2 and 11.9 to 93.8 mg/100 g in vegetable oil, legumes, nuts and cereals, respectively. 34 Considering theses values, aroeira may be considered a good source of such components. β-sitosterol, stigmasterol, and campesterol were also determined in red pepper (Capsicum annuum L.) fruits.…”
Section: Phytosterolsmentioning
confidence: 99%